IMPLEMENTATION OF CHILD-FRIENDLY SCHOOL-BASED DEEP LEARNING AND GOOD HABITS BY PPL STUDENTS IN ELEMENTARY SCHOOLS - Feri Tirtoni; Amelia Puja Noviyanti; Berlian Ayu Tikasari; Amalia Habibah; Siti Nisaaul Akmaliyah (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study examines the implementation of deep learning based on child-friendly school principles and positive habits by students in the Educational Field Practice Program (PLP) at the elementary school level, within the Merdeka Curriculum, which prioritizes meaningful learning and character development. The background of the study emphasizes the challenges facing 21st-century education in Indonesia, where conventional learning models still dominate, while the concept of childfriendly schools has not yet been fully integrated with deep learning and the formation of beneficial habits. A research gap was identified in the lack of an integrated analysis of the role of PLP students as innovative changemakers. The primary objective was to describe and examine the contribution of PLP students in shaping a child-friendly school culture through deep learning approaches (e.g., group discussions and analytical thinking) and positive habits (such as group prayer, morning literacy, and discipline). A descriptive qualitative approach was employed, involving 25 third-grade students at Muhammadiyah 1 Krian Elementary School.